Phase-field simulations of multi-component solidification and coarsening based on thermodynamic datasets - Schulz, Sebastian (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2017)
The utilization of thermodynamic and mobility data plays a major role in phase-field modeling. This work discusses different formulations for the thermodynamic quantities of a grand potential model along with practices to determine parameters from datasets. The framework is used to study solidification of Al-Si-Mg for a variation of composition, diffusivities and surface energy anisotropies. To verify the simulations, they are compared with solidification theories.